Small uncountable powers of the Sorgenfrey line may not be weakly pseudocompact - Rojas-Hernández, Reynaldo (Topology Proceedings, 2024)
It is established that if Martin’s Axiom M A(κ) holds for some cardinal κ, then the κ-power S^κ, of the Sorgenfrey line S, is not weakly pseudocompact.